E-Learning Management System for Secondary School in Malaysia. - Abdul Rashid, Nur Aini; Majid, Omar; Chow, Shiao Yen (Universiti Sains Malaysia, 2002)
With the advancement of Information communication Technology in Malaysia, teachers should take advantage to upgrade their teaching techniques. Students should be allowed to learn anytime. anywhere and at their own peace. Teachers should be able to keep a collection of test/tutorial questions online.